Pengelolaan Zakat Di Daarut Tauhiid Kota Lubuklinggau Dalam Tinjauan Undang – Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Fitrido, Kurnia; Yusefri, Yusefri; Hartini, Hartini (Berasan: Journal of Islamic Civil Law, 2022)
The purpose of this study is to find out the management of Zakat, Infak and Sadaqah in  Daarut Tauhiid Peduli Lubuklinggau and the perspective of Law No. 23 of 2011  as the basis for the presence of the Amil Zakat Institution (LAZ) Daarut Tauhiid  Peduli Lubuklinggau City.  The method used in this study is a qualitative method. Data collection was carried out using field research observations, interviews and documentation at the Amil Zakat Daarut Tauhiid Lubuklinggau Institute. The collected data is then analyzed using descriptive analysis, reduced, then dissented or inferred.  The results  of the study are the management of zakat, infak and alms at the Daarut Tauhiid Peduli Lubuklinggau amil zakat institution in terms of collection, distribution, utilization, has referred to Law No. 23 of 2011.  This is based on the periority scale by paying attention to equity, justice and territoriality. Meanwhile, the utilization of zakat has also been distributed for several program developments such as productive efforts on the economic pillar, namely resilient villages so that it becomes an added value for the existence of the Amil Zakat Daarut Tauhiid Peduli Lubuklinggau Institution to become the community's choice in zakat management.